PENGGUNAAN METODE JARIMATIKA DAN DRILL UNTUK MENINGKATKAN HASIL BELAJAR MATERI OPERASI PERKALIAN PADA SISWA KELAS III MI NU MIFTAHUT THOLIBIN MEJOBO KUDUS - Elya Umi Hanik; Muhammad Rizky Pratama; Uswatun Khasanah; Hapsari Cahyaning Putri (JURNAL ILMIAH PENDAS: PRIMARY EDUCATION JOURNAL, 2021)
This study aims to improve the learning outcomes of students' mathematical multiplication operations using the drill method and the Jarimatika method. This classroom action research was carried out in 2 cycles with four stages, namely: planning, implementation, observation, reflection. The subjects of this study were the class III students of MI Miftahut Tholibin Mejobo Kudus as many as 17 students. This study uses qualitative descriptive analysis techniques and quantitative descriptions. The results showed that the use of the drill method and the Jarimatika method in arithmetic multiplication operations material could improve student learning outcomes which was marked by an increase in mastery, namely the first cycle (64%) with an average value of 68.82, while in the second cycle (88%) with an average value of 87.64 and declared classically successful 88%.